Peroxisomal Fatty Acid Uptake Mechanism in Saccharomyces cerevisiae - van Roermund, Carlo W. T. (American Society for Biochemistry and Molecular Biology, 2012)
Peroxisomes play a major role in human cellular lipid metabolism, including fatty acid β-oxidation. The most frequent peroxisomal disorder is X-linked adrenoleukodystrophy, which is caused by mutations in ABCD1. The biochemical hallmark of X-linked adrenoleukodystrophy is the accumulation of very long chain fatty acids (VLCFAs) due to impaired peroxisomal β-oxidation. Although this suggests a role of ABCD1 in VLCFA import into peroxisomes, no direct experimental evidence is available to substantiate this. To unravel the mechanism of peroxisomal VLCFA transport, we use Saccharomyces cerevisiae as a model organism. Here we provide evidence that in this organism very long chain acyl-CoA esters are hydrolyzed by the Pxa1p-Pxa2p complex prior to the actual transport of their fatty acid moiety into the peroxisomes with the CoA presumably being released into the cytoplasm. The Pxa1p-Pxa2p complex functionally interacts with the acyl-CoA synthetases Faa2p and/or Fat1p on the inner surface of the peroxisomal membrane for subsequent re-esterification of the VLCFAs. Importantly, the Pxa1p-Pxa2p complex shares this molecular mechanism with HsABCD1 and HsABCD2.